2014
DOI: 10.1088/1674-4527/14/6/009
|View full text |Cite
|
Sign up to set email alerts
|

New vacuum solar telescope and observations with high resolution

Abstract: The New Vacuum Solar Telescope (NVST) is a 1 meter vacuum solar telescope that aims to observe the fine structures on the Sun. The main tasks of NVST are high resolution imaging and spectral observations, including the measurements of solar magnetic field.NVST is the primary ground-based facility of Chinese solar community in this solar cycle. It is located by the Fuxian Lake of southwest China, where the seeing is good enough to perform high resolution observations. In this paper, we first introduce the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
187
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 281 publications
(189 citation statements)
references
References 13 publications
0
187
0
2
Order By: Relevance
“…Here we use joint observations between IRIS and the Chinese 1 m New Vacuum Solar Telescope (NVST, Liu et al 2014) to examine the possible connection between IBs and EBs. The NVST belongs to a new generation of large and high-technology solar facilities of China and one of the postfocus instruments is the Multi-channel High Resolution Imaging System, including a H , G-band, TiO band, Ca II 8542 Å, and He I 10830 Å wavelengths (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here we use joint observations between IRIS and the Chinese 1 m New Vacuum Solar Telescope (NVST, Liu et al 2014) to examine the possible connection between IBs and EBs. The NVST belongs to a new generation of large and high-technology solar facilities of China and one of the postfocus instruments is the Multi-channel High Resolution Imaging System, including a H , G-band, TiO band, Ca II 8542 Å, and He I 10830 Å wavelengths (Xu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Yang et al (2015) and Bharti (2015) independently identified a bright front with TR temperatures ahead of the chromospheric surges above a light bridge. The bright front can be seen in the 1330 and 1400 Å slit-jaw images of IRIS, while the wall-like surges are visible in chromospheric images such as the Hα images taken by the new vacuum solar telescope (NVST, Liu et al 2014) and the 2796 Å slit-jaw images taken by IRIS. Figure 3 shows an example of the surge and the bright front ahead of the surge.…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 99%
“…The 98.5 cm New Vacuum Solar Telescope (NVST) at Fuxian Lake is a Chinese telescope, which has recently been upgraded for high-resolution observations (Yang et al 2014;Liu et al 2014b). …”
Section: Nvstmentioning
confidence: 99%